2016
DOI: 10.1007/s10681-016-1720-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical indicators of drought tolerance in the common bean (Phaseolus vulgaris L.)

Abstract: The common bean (Phaseolus vulgaris L.) is an important crop that is often planted in areas that suffer from low water availability, leading to significant reductions in productivity. The breeding of genotypes better able to tolerate such conditions requires the efficient incorporation of resources present in germplasm banks. To this end, we investigated the responses of thirty bean genotypes to intermittent drought stress, with the aim of identifying biochemical markers for drought tolerance. The genotypes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
3
33
0
1
Order By: Relevance
“…The effects of climate changes on yield were previously reported [1], and it was shown that severe drought stress can lead to crop losses of up to 90% [10][11][12]. While there has been considerable progress in understanding the sensitivities of crop yield to climate change, evaluation of climate change factors such as CO 2 , elevated temperature, or drought on seed nutrition remains rather limited [13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of climate changes on yield were previously reported [1], and it was shown that severe drought stress can lead to crop losses of up to 90% [10][11][12]. While there has been considerable progress in understanding the sensitivities of crop yield to climate change, evaluation of climate change factors such as CO 2 , elevated temperature, or drought on seed nutrition remains rather limited [13].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of involvement of these sugars in drought tolerance are still not fully understood [19][20][21]. The accumulation of proline, amino acids, and organic acid such as malic acid, fumaric acid, and citric acid is also a common biochemical indicator occurring at high level under drought stress [12]. The accumulation of these compounds is a part of the mechanism of osmotic adjustment to maintain water potential gradient under drought conditions and to protect subcellular structure from the damaging effects of drought stress [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations